ANALYZING OF SPEECH ACT IN THE A MONSTER CALLS MOVIE - Basuki Santoso, Daffa Akbar Dejavu Santoso (Universitas Negeri Surabaya, 2025)
ABSTRACT Speech act is an utterance that contains action as a function of communication that considers aspects of the speech situation. The purpose of this study is to analyze the types of speech acts found in the film “A Monster Calls”. This research uses qualitative research. There are some data containing speech acts in the movie “A Monster Calls”. There are several types of speech acts found in this movie is namely locutionary speech acts, illocutionary speech acts, and perlocutionary speech acts. these speech acts have their own meaning in conveying sentences to give the response. but in this study it is more focused in illocutionary speech acts that contain the intent and function of speech power. These acts are identified as speech acts that are to inform something and do something, and contain the purpose and power of speech Each type of speech act conveys a different meaning. The results of this study are taken from the script of the main character named Conor and the actions with other characters through utterances that are in the dialogue.